Managing women with postnatal depression: perceptions of Malaysian healthcare practitioners - Mohd Arifin, Siti Roshaidai; Cheyne, Helen; Maxwell, Margaret (2020)
Purpose: To explore the understanding of PND and experience of managing women with PND among Malaysian healthcare practitioners (HCPs). Methods: Using an exploratory qualitative design, 18 HCPs working in maternal and child health clinics and a female psychiatric ward in Kuala Lumpur were individually interviewed. Interview data were transcribed verbatim and the transcripts were analysed using framework analysis. Results: HCPs reported that their management of PND was limited by the absence of a specific screening tool and a clear policy and guidelines that they could refer to. Stigma connected to PND making the professional treatment will be the choice only when the conventional (traditional) treatment failed. Conclusion: A relevant screening tool to assess PND among Malaysian women is urgently needed. Professional training and continuous education on PND would be beneficial in fostering quality of care and creating public awareness within the Malaysian healthcare system.